Reading Proverbs 13:23 in Texts and Contexts of Africa’s Poverty: A Theoretical Framework - Wabyanga, Robert Kuloba (Old Testament Essays, 2022)
The Masoretic text of Prov 13:23 (רָב־אֹ֭כֶל נִ֣יר רָאשִׁ֑ים וְיֵ֥שׁ נִ֜סְפֶּ֗ה בְּלֹ֣א מִשְׁפָּֽט) highlights the absence of mishpat (מִשְׁפָּט) as the cause of the poverty of the poor. This article reads Prov 13:23 in conversation with the contemporary conceptualisation of economic poverty. The concept of mishpat (מִשְׁפָּט) is theorised and hermeneutically applied to the issue of poverty in Africa. The key questions under investigation are: What is mishpat in the text and its context? How should mishpat be read in the African context? How does the biblical understanding of the poor and mishpat inform responses to Africa’s poverty? In this study, the assumptions are that poverty in Africa is the result of both socio-economic and political injustices of the West and Africans themselves. Africans are agents of their own poverty. The study employs a hermeneutical and multidisciplinary approach, drawing examples from the social sciences. https://doi.org/10.17159/2312-3621/2022/v35n2a10